舌扁平上皮癌二次症例における救済手術の予後—一次症例との比較より - 長谷川, 泰久; 後藤, 満雄 (日本口腔外科学会雑誌, 2010)
Reported rates of oral cancer recurrence range from 25 % to 48 %. Improving the treatment outcomes of these cases would lead to a better prognosis of oral cancer. The aim of this study was to evaluate prognostic factors and the outcomes after salvage surgery in patients with squamous cell carcinoma of the tongue. We analyzed 110 patients who underwent primary radical surgery (primary cases) and 77 previously treated patients who underwent salvage surgery (secondary cases) between March 1985 and March 2000. A 5-year survival curve was constructed using the Kaplan-Meier method. Statistical significance was evaluated with the logrank test. A Cox proportional-hazards regression analysis was used to identify prognostic factors. Recurrence rates in primary/secondary cases were 17.3 %/9.1 % for delayed neck metastasis, 10.0 %/15.6 %for local recurrences, 5.5 %/10.4 % for regional recurrences, and 3.6 %/2.6 % for locoregional recurrences.Overall 5-year survival rates were 78.9 % for primary cases and 67.5 % for secondary cases. Survival rates differed significantly between rN − (82.9 %) and rN + (54.8 %) secondary cases treated by salvage surgery. Significant prognostic factors on multivariate analysis were the extracapsular spread of cervical lymph node metastasis in both primary and secondary cases and the pN category in secondary cases. In conclusion, extracapsular spread was a significant predictor of survival. Salvage surgery cases with neck recurrence had poor outcomes.